KONSEP TASAWUF DALAM ISLAM DAN APLIKASINYA DALAM MEMBANGUN NILAI-NILAI ETIKA SOSIAL BAGI PESERTA DIDIK ERA MODERN - Firman Jumbati; Silvia Isna Auladah Herman; Imron Rossidy; Muhammad Inam Esha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of the modern era has brought various challenges to the formation of students' social ethics, including moral degradation and spiritual crises. Therefore, the concept of tasawuf (Islamic Sufism) offers a relevant approach to addressing these issues. This study aims to: (1) identify the concepts of tasawuf in Islam that are relevant to students' social ethical values in the modern era, and (2) analyze their application in fostering students' social ethical values. The research employs a qualitative descriptive approach through library research, involving the analysis of relevant classical and contemporary literature. The findings reveal two main points: (1) the concepts of tasawuf, such as tazkiyatun nafs (self-purification), muhasabah (self-reflection), and mujahadah (self-discipline), play a significant role in developing students' social ethical values in modern life; and (2) the application of these concepts strengthens and deepens essential social ethical values, including honesty, empathy, solidarity, and social responsibility among students. It can therefore be concluded that the concepts of tasawuf and their practical application effectively reinforce social ethical values, contributing to the development of students with noble character who are better equipped to face the moral and spiritual challenges of the modern era.